EDUKASI PEMBERIAN MAKANAN TAMBAHAN KEPADA IBU BALITA TERHADAP STATUS GIZI BALITA DI POSYANDU MUTIARA ANANDA DESA WONOROTO KABUPATEN PURWOREJO - Sholichah, Nur; Dyah Rukmala Suryadi, Intan; Yuliana, Putri (Jurnal Komunikasi Kesehatan, 2025)
Nutrition is one of the determining factors of human resource quality. The role of nutrition has been proven by various studies. Nutritional disorders in early human life will affect the qualityof life later. One of the programs initiated by the government is the Provision of Additional Food(PMT). To provide education on providing additional food to mothers of toddlers regarding thenutritional status of toddlers. This type of research is a pre-experimental design with a One GroupPretest-Postest Design. The population in this study was 30 mothers of toddlers. The samplingtechnique used purposive sampling. The time of the study was July 15 - August 19, 2024. Dataanalysis used the Paired t test. The results of the data analysis obtained a t value of 0.002 and aprobability of 0.000 (smaller than alpha 0.05). The level of knowledge of respondents after beinggiven PMT counseling was 70.9% from 63.8% before being given education. So, there is aninfluence of PMT education on the knowledge of mothers of toddlers about PMT. SuggestionThe results of the study can be used as a source of knowledge and strategies for mothers oftoddlers in providing midwifery care to families and toddlers.